Susceptibility of anaerobic bacteria from several French hospitals to three major antibiotics. - Dubreuil, L (1984)
The in vitro activity of cefoxitin was compared with those of metronidazole and clindamycin against 322 strains of anaerobic bacteria collected from several hospitals during 1982 and tested by an agar dilution method. Metronidazole and cefoxitin inhibited at least 89% of strains tested, whereas clindamycin was less active.